A study on acute urinary retention in patients with benign prostatic hyperplasia at a rural setup - Addepalli, Jagadeeswar; K S, Balasubramanya; Francis, John M.; Thanneru, Karthik (International Surgery Journal, 2019)
Background: Acute urinary retention (AUR) is one of the most significant complications of benign prostatic hyperplasia (BPH). Aim was to discuss the management of AUR in BPH in a rural setup. Methods: It was a prospective study, at PESIMSR, Kuppam, on 100 BPH patients who presented to the ER or OPD with AUR from November 2016 to June 2018. All were catheterized initially. Patient clinical characteristics, prostate size, type of AUR and management one (type of catheterization, hospitalization, trial without catheterisation (TWOC), use of medication, immediate and elective surgery) were recorded. Results: Mean age was 68.33±9.1. Most patients (74 %) had spontaneous AUR and rest had precipitating factors. A per-urethral catheter (PUC) was inserted in most cases (96%), rest had supra-pubic cystostomy (SPC). Patients with prostate volume of <30 ml (n=8) were started on alpha-blocker (AB) alone and those with >30 ml were given AB with 5 alpha-reductase inhibitor (ARI) combination. TWOC had an overall success rate of 72% (n=72), of them 38 opted for elective surgery. TWOC failed in 28 patients who were re-catheterized and underwent transurethral resection of prostate (TURP) on an elective basis. 66 out of 100 patients underwent TURP in the course of management of AUR in BPH. Conclusions: Management of AUR in BPH patients in real-life practice in a rural setup hospital has been evaluated. It shows that urethral catheterization, medication, TWOC and finally continuing medical management or planning TURP based has become standard practice.